Discourse Network Analysis on Delaying Elections in President Joko Widodo's Era - Neli Elislah (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
The postponement of elections became an issue that was widely discussed during President Jokowi's presidency, resulting in increased public distrust of politicians and politics itself and created political cynicism. Meanwhile, public distrust and political cynicism greatly influence public policies created by political leaders. Through discourse network analysis, this study wants to see the relationship between the discourse on postponing elections and the relationship between discourse and public policy. The novelty of the previous research on postponing elections lies in the theory of political cynicism which is very relevant in explaining the process of forming policies on this issue. This research looks at during (January-April 2022), the issue of postponing elections produces conflict discourse, this also explains that conflict discourse often occurs in controversial policies. This controversial policy conflict brought the public to a high level of distrust, directly proportional to the political cynicism that occurred. Finally, the neutral discourse that was present reminded political leaders to focus more on urgent problems because the impact of political cynicism also made it difficult for political leaders to make decisions.